Peranan Lembaga Penyiaran Publik RRI Medan Dalam Menghadapi Persaingan Informasi Pada Era Digital - Asri Lestari; Wahyu Syarvina (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
As technology advances, communication is a very important aspect of technology. The level of radio competition at radio stations in big cities is quite high in winning the hearts of the audience, so this study aims to analyze the role of the RRI Medan Public Broadcasting Institution in being able to retrieve information on the interests of listeners in the digital era through the application platform that has been made, namely RRI PLAY GO so that generations X and Z can hear information through their respective Gadgets or Cellphones. This study uses a descriptive analysis model with the data obtained as testing material. In this research, a data collection method is needed to answer all the proposed research problems. The results show that the role of RRI PLAY GO is to retrieve enough information to increase listeners' interest in the digital era.